"Fat is really a four‐letter word": Exploring weight‐related communication best practices in children with and without disabilities and their caregivers. (15th May 2018) - McPherson, A. C.; Knibbe, T. J.; Oake, M.; Swift, J. A.; Browne, N.; Ball, G. D. C.; Hamilton, J.
Abstract: Background: Health care professionals play a critical role in preventing and managing childhood obesity, but the American Academy of Pediatrics recently stressed the importance of using sensitive and nonstigmatizing language when discussing weight with children and families. Although barriers to weight‐related discussions are well known, there are few evidence‐based recommendations around communication best practices. Disability populations in particular have previously been excluded from work in this area. The objectives were to present the findings of a recent scoping review to children with and without disabilities and their caregivers for their reactions; and to explore the experiences and perceptions of the children and their caregivers regarding weight‐related communication best practices. Methods: Focus group and individual interviews were conducted with 7–18‐year olds with and without disabilities and their caregivers. The interview guide was created using findings from a recent scoping review of weight‐related communication best practices. Inductive thematic analysis was employed. Results: Eighteen children (9 boys; 7 children with disabilities) and 21 caregivers (17 mothers, 1 step‐father, 3 other caregivers) participated in 8 focus group and 7 individual interviews. Preferred communication strategies were similar across those with and without disabilities, although caregivers of children with autism spectrum disorder endorsed more concrete approaches. Discussions emphasizing growth and health were preferred over weight and size. Strengths‐based, solution‐focused approaches for weight conversations were endorsed, although had not been widely experienced. Conclusion: Perceptions of weight‐related communication were similar across stakeholder groups, regardless of children's disability or weight status. Participants generally agreed with the scoping review recommendations, suggesting that they apply broadly across different settings and populations; however, tailoring them to specific circumstances is critical. Empirical evaluations are still required to examine the influence of weight‐related communication on clinically important outcomes, including behaviour change and family engagement in care.